Speaking With Debate Methods: Class Action Research Study - Nana Fauzana Azima (International Journal of Educational Dynamics, 2019)
The purpose of this study is to describe the improvement in speaking skills of students using the debate method in class V of SDN 10 Sapiran Bukittinggi. The types of research are PTK, qualitative and quantitative approaches. The research subjects were teachers and 26 fifth grade students of SDN 10 Sapiran Bukittinggi. Planning cycle I obtained a percentage of 82.14%, cycle II 92.85%. The implementation of the first cycle was 81.25%, the second cycle was 95%. Speaking skills in cycle I 78.54%, cycle II 93.15%. Thus, the debate method can improve the speaking skills of fifth grade students of SDN 10 Sapiran Bukittinggi.